Creatinine values during a competitive season in elite athletes involved in different sport disciplines - Banfi, G.; Del Fabbro, M.; Lippi, G. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim: The authors aimed at studying creatinine concentrations in elite male athletes of rugby, alpine ski and cyclism, characterized from different Body Mass Index (BMI) to evaluate modifications during the competitions season. Methods: Creatinine was measured by Jaffe method in 44 top-level athletes (18 rugbyists, 13 skiers, and 13 cyclists) before the start of training and competitions and during the competitions season, three times for rugbyists and skiers, and two times for cyclists. Results: Creatinine concentrations were related to body mass and were significantly different among the groups of athletes of the three sports. Analysis of variance showed significant differences among groups of athletes practising different sports (P<0.0001). The analysis for repeated measures demonstrated significant differences for rugby (P<0.005) and ski (P<0.02), but not for cycling (P=0.25). Conclusion: The interpretation of the creatinine concentrations in athletes should take in account the kind of sport practised, the BMI, and also the possible variations during the season. The reference intervals used for general population can not be used for athletes.